Praktyczne aspekty budżetowania w samodzielnym publicznym zakładzie opieki zdrowotnej - Lewicka, Beata (The Practical Aspects of Budgeting in Independent Public Health Care Institution, 2006)
The law reform of health care industry in Poland, the marketing of medical services, the increased competition of medical institutions make independent public health care institution managers search for new ways of executing these subjects. In the article, budgeting was presented as a managment tool that helps running an independent public health care institution more effectively.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 233-241